Wideband partially reflecting surface antenna with broadband RCS reduction. Issue 6 (26th February 2018) - Jiang, Hao; Xue, Zhenghui; Leng, Meifang; Li, Weiming; Ren, Wu
Abstract : A wideband partially reflecting surface (PRS) antenna with broadband reduced radar cross‐section reduction (RCSR) is demonstrated in this study. The proposed antenna consists of a microstrip patch, a triple‐layer PRS, and a defective frequency selective surface (FSS) ground plane. The PRS is the combination of a dual‐layer RS and an absorbing surface, which is located nearly one‐half of the wavelength above the ground. The RS is a complementary structure with a positive phase gradient, so the wideband gain enhancement is accomplished. In addition, a defective ground plane, which consists of the band‐stop FSS, is designed to obtain an enhanced RCSR. Experimental results illustrate the impedance bandwidth of the presented antenna is 10.2% and the peak gain is 14.4 dBi at 6.3 GHz. Comparing to the patch antenna of the same dimension, a broadband RCSR from 8 to 18 GHz is obtained, where many types of radars are strategically deployed, and the average number of RCSR is 12.6 dB. The proposed PRS antenna is a promising candidate for absorbing elements in scientific and military applications.